2022
DOI: 10.1007/s00221-022-06333-7
|View full text |Cite
|
Sign up to set email alerts
|

Instant improvement in monaural spatial hearing abilities through cognitive feedback

Abstract: Several studies report that sound localization performance of acute and chronic monauralized normal-hearing listeners can improve through training. Typically, training sessions are administered daily for several days or weeks. While this intensive training is effective, it may also be that monaural localization abilities improve instantly after providing explicit top-down information about the direction dependent change in timbre and level. The aim of the present study was to investigate whether cognitive feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…A recent study in children with congenital conductive UHL showed that they may rely on monaural spectral cues for horizontal sound localisation ( 35 ). Context of listening cues can also be important for sound localisation and would be interesting to investigate ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in children with congenital conductive UHL showed that they may rely on monaural spectral cues for horizontal sound localisation ( 35 ). Context of listening cues can also be important for sound localisation and would be interesting to investigate ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for the former the E rms of chance responses could range from 32 deg to 63 deg, while for our study it ranges between 48 deg and 73 deg. Second, top-down cognitive factors and strategies (e.g., influenced by instruction, task, speaker layout and (in)visibility) may introduce significant experimental differences ( Arras et al, 2022 ). Third, sounds of different frequency content, duration, and power spectra have been used (speech vs broadband white noise vs narrowband sounds).…”
Section: Discussionmentioning
confidence: 99%
“…Also, stimuli have included broadband noise ( Dillon et al 2017b ), high-pass/low-pass filtered stimuli ( Dorman et al 2015 ; Mertens et al 2016 ; Dirks et al 2019 ), words ( Firszt et al 2012a , b ), and sentences ( Arndt et al 2011 ). It is important to note that the results may be influenced by the methodological approach, such as whether leveling roving of the stimulus is used to limit the sole use of level cues ( Middlebrooks & Green 1991 ; Wightman & Kistler 1997 ; Arras et al 2022 ). Taken together, investigation is needed for clinically feasible test configurations that can assess sound source localization within the typical clinical setup and an optimal test battery.…”
Section: Audiologic Assessmentmentioning
confidence: 99%